Approaches to the use of Markov random processes in mathematical models of project management harvesting of agricultural products - Ковальчик, Юрій Іванович; Ковалишин, Степан Йосипович; Тимочко, Василь Олегович (Eastern-European Journal of Enterprise Technologies, 2012)
The expedience and methodology of casual Markov processes in models of productivity determination of harvesting machinery are grounded in the project management of agricultural production harvesting